Teknik Pengolahan Lahan dan Pembuatan Bedengan - Telaumbanua, Iman Victor; Nazara, Linda Hepi; Lawolo, Toni Yusman; Lawolo, Todermanto; Harefa, Forniwati; Waruwu, Weldimen; Lase, Natalia Kristiani; Telaumbanua, Elemonoku D. (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
This research aims to develop effective land processing and bed making techniques in Dahana Village, West Gunungsitoli District. Processing techniques include land clearing, plowing with a cultivator, and manual loosening of the soil. The beds are formed with standard dimensions and equipped with a drainage system to prevent waterlogging. The research results showed an improvement in soil quality with porosity increasing from 35% to 45%, and soil mass density decreasing from 1.4 g/cm ³ to 1.1 g/cm ³. The creation of 45 raised beds with an efficient drainage system has also succeeded in increasing the efficiency of land use and water management. This research recommends the use of organic mulch, drip irrigation, and digital monitoring systems to increase agricultural productivity.